A study on how to utilize smart containers based on the sharing economy - Dulguun Banzragch(반즈라그츠 둘군); Hyung-Rim Choi(최형림); Chae-Soo Kim(김채수) (한국정보전자통신기술학회 논문지, 2024)
기술 발전은 컨테이너 해운 산업의 디지털 혁신을 이끌어 스마트 컨테이너를 가능하게 했습니다. 스마트 컨테이너는 공급망 효율성, 보안성, 지속 가능성을 향상시키지만, 높은 비용이 보급의 장애물로 작용하고 있습니다. 본 연구는 스마트 컨테이너의 공유를 해결책으로 제시하며, 해운 회사를 군집 분석을 통해 군집화하여 실현 가능성을 높이기 위한 방법을 실증적으로 제시합니다. 한국의 26개 해운 회사 웹사이트에서 데이터를 수집하고 SPSS의 k-means 알고리즘을 사용하여 군집 분석을 실시한 결과, 세 개의 클러스터가 도출되었습니다. 첫 번째 클러스터는 주요 항만 근처의 수익성이 높은 회사들, 두 번째 클러스터는 경제적 성과가 높은 항만 근처의 회사들, 세 번째 클러스터는 수도권에 위치한 수익성이 중간 회사들로 구성되었습니다. 군집 분석을 활용하면 스마트 컨테이너 공동 하치장 운영 등의 기초 데이터를 제공할 수 있음을 보여줍니다. Technological advancements have driven a digital transformation in the container shipping industry, leading to the development of smart containers equipped with low-cost tracking and monitoring devices. These containers offer enhanced efficiency, security, and sustainability across the supply chain; however, their high cost hinders widespread adoption. This study proposes the sharing of smart containers as a solution and empirically demonstrates a method for clustering shipping companies—potential smart container customers—into groups to improve feasibility. Data from the websites of 26 South Korean shipping companies were collected and analyzed using SPSS’s k-means algorithm. The analysis revealed three clusters: Cluster 1, consisting of profitable companies near major ports with high capital and asset ratios; Cluster 2, with companies near ports- higher economic performance; and Cluster 3, located in the metropolitan area with medium profitability. The study suggests that cluster analysis can help government bodies and associations target smart container demand, providing foundational data for shared container storage systems. KCI Citation Count: 0